3D Contrast Enhancement-MR Angiography for Imaging of Unruptured Cerebral Aneurysms: A Hospital-Based Prevalence Study - Li, Jing; Shen, Bixia; Ma, Chao; Liu, Li; Ren, Li; Fang, Yibin; Dai, Dongwei; Chen, Shiyue; Lu, Jianping (PloS one, 2014)
Contrast enhanced MRA (CE-MRA) can help to overcome the limitations of other techniques to clearly display the details of cerebral aneurysms at 1.5-T MR system. We investigated the prevalence of unruptured cerebral aneurysms (UCAs) using three dimensional (3D) CE-MRA in a tertiary comprehensive hospital in China. The cases were prospectively recorded at our hospital between February 2009 and October 2010. 3D CE-MRA, interpreted by 2 observers blinded to the participants' information, was used to identify the location and size of UCAs and to estimate the overall, age-specific, and sex-specific prevalence. Of the 3993 patients (men: women = 2159:1834), 408 UCAs were found in 350 patients (men: women = 151:199). The prevalence was 8.8% overall (95% CI, 8.0-10.0%), with 7.0% for men (CI, 6.0-8.0%) and 10.9% for women (CI, 9.0-12.0%). The overall prevalence of UCAs was higher in women than in men (P<0.001) and increased with age both in men and women. Prevalence peaked at age group 75-80 years. Forty-two patients (11.7%) had multiple aneurysms, including 10 (2.9%) male patients and 32 (9.1%) female patients. The most common site of aneurysm was the carotid siphon, and most lesions (71.3%) had a maximum diameter of 3-5 mm. This hospital-based prevalence study suggested a high prevalence (8.8%) of UCAs and most lesions (71.3%) had a maximum diameter of 3-5 mm observed by 3D CE-MRA. Because the rupture of small cerebral aneurysms was not uncommon, an appropriate follow-up care strategy must be formulated.